2001
DOI: 10.1002/jso.1088
|View full text |Cite
|
Sign up to set email alerts
|

Gamma probe‐directed lymphatic mapping and sentinel lymphadenectomy in primary melanoma: Reliability of the procedure and analysis of failures after long‐term follow‐up

Abstract: We concluded that gamma probe-directed sentinel lymph node biopsy is a straightforward procedure which can be done in the outpatient setting and facilitates management of patients with cutaneous malignant melanoma. It allows the surgeon to identify all basins at risk for metastatic disease and the location of the sentinel node(s) in relation to the basin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 18 publications
2
19
1
2
Order By: Relevance
“…We found in our consecutive series that SLN biopsy is a sensitive method to identify micrometastases as at least one SLN was identified at operation in 98.2% (274 of 279 cases) compared to reported rates ranging from 88% to 99% (Table V). In the 274 cases, we removed 614 SLNs, a median of 2 per patient, and in 22% there was drainage to more than one lymph node basin, a finding in agreement with other studies [8,11,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…We found in our consecutive series that SLN biopsy is a sensitive method to identify micrometastases as at least one SLN was identified at operation in 98.2% (274 of 279 cases) compared to reported rates ranging from 88% to 99% (Table V). In the 274 cases, we removed 614 SLNs, a median of 2 per patient, and in 22% there was drainage to more than one lymph node basin, a finding in agreement with other studies [8,11,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…Nowadays, a standardized protocol combines preoperative dynamic lymphoscintigraphy and intraoperative blue-dye injection with gamma probe guidance [5]. Nevertheless, a prospective series of 103 melanoma patients showed that an isotopic mapping alone based on dynamic lymphoscintigraphy and gamma probe was a reliable procedure [17]. These results confirmed previous findings suggesting good success rates when using the radiotracer method singly Table 8 n.s.…”
Section: Discussionsupporting
confidence: 82%
“…The association of technetium-labeled sulfur colloid and blue dye injection techniques in adults proved to have an overall accuracy rate of 96-100% and over 90% in predicting axillary metastases in cases with breast cancer and in the staging of malignant melanoma respectively [9,10,26,27]. Our data showed that both the procedures can be performed safely in childhood allowing accuracy in the identification of the sentinel node, however our figures cannot support a benefit of the association of the two techniques.…”
Section: Discussionmentioning
confidence: 54%